Positive electrode material, positive electrode plate and lithium ion battery
By regulating the coating layer thickness and particle ball shape of the positive pole material, combined with the moderate granularity, the problem of granular crushing of the orthopedic pole sheet under high -pressure solid density, realizing the high magnification and cycle performance, while having high voltage density density density density density And high gram capacity.
Patent Information
- Application Number
- CN202411138586.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-28
AI Technical Summary
The existing positive electrode sheets are prone to breaking up active substance particles under high compaction density, resulting in performance attenuation, which in turn affects the rate performance and cycling performance of the battery cell.
By regulating the coating layer thickness H and particle spherical S of the positive electrode material, it can satisfy it 4≤H*S ≤ 155, 6nm ≤H ≤ 16nm, 0.6 ≤S ≤ 1, and control the particle size D50 in the range of 6 μm to 16 μm. , Enhance the structural strength of the positive material, avoid crushing particles under high pressure.
While the positive poles, while the high -voltage solid density and the high gram capacity, maintain a good multipliers and circulating performance, avoiding performance attenuation.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material, a positive electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have become an ideal power source for electric vehicles and energy storage due to their outstanding advantages such as high energy density, excellent cycle life, high operating voltage, low self-discharge rate, and environmental friendliness. At present, the energy density of lithium-ion batteries can already support a range of 500km on a single charge, which can meet most travel needs. With the continuous increase in users' demand for the range of electric vehicles, in order to meet users' higher demand for the range of electric vehicles, it is necessary to produce positive electrode sheets with higher energy density. In order to enable the positive electrode sheet to achieve high energy density, it is necessary to roll the positive electrode sheet to obtain a positive electrode sheet with high compaction density and high gram capacity. However, in the preparation of existing positive electrode sheets, when the compaction density of the positive electrode sheet is too high, it is easy to cause the active material particles of the positive electrode sheet to break, resulting in a significant attenuation of performance, which in turn leads to poor rate performance and cycle performance of the manufactured battery cell. Summary of the invention
[0003] The present invention provides a positive electrode material and a positive electrode plate, aiming to achieve that the positive electrode plate still has good rate performance and cycle performance under high compaction density.
[0004] To achieve the above-mentioned purpose, the present invention provides a positive electrode material, which includes a core body and a coating layer located on the surface of the core body, the thickness H of the coating layer and the sphericity S of the particles of the positive electrode material satisfy the relationship: 4≤H*S≤15, the value range of H is 6nm≤H≤16nm, the value range of S is 0.6≤S≤1, and the particle size D50 of the positive electrode material is in the range of 6μm≤D50≤16μm.
[0005] The present invention adjusts the coating thickness H and particle sphericity S of the positive electrode material with a coating layer within a specific range so as to satisfy 4≤H*S≤15, 6nm≤H≤16nm, and 0.6≤S≤1, and adjusts the particle size D50 of the positive electrode material within the range of 6μm to 16μm, so that the positive electrode material has a higher structural strength, and avoids the situation in which the positive electrode material is crushed under high-pressure rolling and causes performance degradation, so that the electrode sheet has good rate performance and cycle performance while having a high compaction density and a high gram capacity.
[0006] In some embodiments, the value range of H is 12nm≤H≤15nm; the value range of S is 0.8≤S≤1; and the value range of D50 is 6μm≤D50≤16μm.
[0007] In some embodiments, H is 15 nm; S is 1; D50 is 16 μm;
[0008] Alternatively, the H is 6 nm, the S is 0.7, and the D50 is 6 μm;
[0009] Alternatively, the H is 10 nm, the S is 0.8, and the D50 is 10 μm;
[0010] Alternatively, the H is 15 nm, the S is 1, and the D50 is 6 μm;
[0011] Alternatively, the H is 12 nm, the S is 0.8, and the D50 is 13 μm;
[0012] Alternatively, the H is 6 nm, the S is 0.7, and the D50 is 16 μm.
[0013] In some embodiments, the chemical formula of the core is Li a Ni x Co y M 1-x-y O 2 , wherein M is Mn or Al, 0.8≤a≤1.5, 0.6≤x≤1, 0≤y≤0.2;
[0014] In some embodiments, the coating layer can be a metal oxide, such as zirconium oxide; it can also be a solid electrolyte, such as lithium titanate, lithium titanium phosphate; it can also be an electrode material, such as LiMn 2 O 4 ), or a conductive polymer such as PANI-PEG. The coating layer has the following functions: 1. It acts as a physical barrier to the core body, inhibiting the side reactions of the core body substance with other substances; 2. It stabilizes the core body structure and reduces the phase change stress; 3. It chemically modifies the core body surface and promotes the charge transfer of ions at the core body interface; 4. It removes HF, prevents chemical corrosion of the electrolyte, and inhibits the dissolution of the transition metal.
[0015] The present invention further provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer is the positive electrode material described above.
[0016] In some embodiments, the positive electrode active material layer further includes a conductive agent and a binder.
[0017] In some embodiments, the conductive agent is selected from at least one of carbon black, conductive graphite, carbon fiber, carbon nanotubes, graphene, and Ketjen black;
[0018] The adhesive is selected from at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate and polyvinyl alcohol.
[0019] The present invention also provides a lithium-ion battery, which includes the positive electrode sheet mentioned above.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adjusts the coating layer thickness H and the particle sphericity S of the positive electrode material with a coating layer within a specific range so as to satisfy 4≤H*S≤15, 6nm≤H≤16nm, and 0.6≤S≤1, and at the same time adjusts the particle size D50 of the positive electrode material within the range of 6μm to 16μm, so that the positive electrode material has a higher structural strength, and avoids the situation in which the positive electrode material is crushed under high-pressure rolling and causes performance degradation, so that the electrode sheet has good rate performance and cycle performance while having a high compaction density and a high gram capacity. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The present invention proposes a positive electrode material, which includes a core body and a coating layer located on the surface of the core body. The thickness H of the coating layer and the sphericity S of the particles of the positive electrode material satisfy the relationship: 4≤H*S≤15, the value range of H is 6nm≤H≤16nm, the value range of S is 0.6≤S≤1, and the particle size D50 of the positive electrode material is in the range of 6μm≤D50≤16μm.
[0023] The present invention controls the particle size D50 of the positive electrode material within the range of 6 to 16 μm, so that the particle size of the positive electrode material remains moderate, and the compaction density of the material is not reduced due to too small a particle size, and the slurry is difficult to disperse and apply during homogenization, and the rate performance of the battery cell during charge and discharge is not reduced due to too large a particle size. In addition, by controlling the coating thickness H of the positive electrode material within the range of 6 to 16 nm, it is possible to avoid the situation where the activity of the positive electrode material is reduced due to too large a coating thickness H, the diffusion resistance of lithium ions is increased, and the rate performance is reduced; it is also possible to avoid the situation where the positive electrode material particles are easily crushed when compacted due to too small a coating thickness H. At the same time, combined with the sphericity of the positive electrode material particles, by adjusting the coating layer thickness H and the particle sphericity S of the positive electrode material within a specific range to satisfy 4≤H*S≤15, the positive electrode material has a higher structural strength, avoiding the situation where the positive electrode material particles are broken under high-pressure rolling and cause performance degradation, so that the electrode has good rate performance and cycle performance while having high compaction density and high gram capacity.
[0024] Several detailed examples and comparative examples are listed below to verify the beneficial effects achieved by the positive electrode material provided by the present invention.
[0025] Example 1
[0026] 1. Preparation of positive electrode materials
[0027] Using the intermittent method: nickel sulfate (NiSO 4 6H 2 O), cobalt sulfate (CoSO 4 7H 2 O) and manganese sulfate (MnSO 4 ·H 2 O) Press Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 The mixed salt solution is prepared in a stoichiometric ratio, with 1M sodium hydroxide solution (NaOH) as the alkali solution and 1M ammonia solution (NH 3 ·H 2O). After the reactor filled with water is filled with nitrogen, the above mixed salt solution is added, wherein the pH in the reactor is maintained at about 11.0±0.1. Subsequently, rapid stirring is performed at a speed of 600-1000 rpm for 10-14 hours. After rapid stirring, low-speed stirring is performed at a speed of 300-500 rpm for 18-26 hours. The obtained solid-liquid mixture is filtered, washed with water, and dried to obtain a precursor. The obtained precursor is mixed with LiOH in a stoichiometric ratio, and sintered once at 780°C in an oxygen atmosphere for 10 hours, and the primary sintering time is washed with water and dried to obtain a primary sintered product. The LiNi 0.8 Co 0.1 Mn 0.1 O 2 and polyvinyl pyrrolidone (PVP), dispersed in a certain amount of ethanol, and 3.3 wt.% of C 8 H 2 0O 4 Ti and 0.83wt.% (NH 4 )H 2 PO 4 The mixture was stirred for 4 h until the ethanol solvent evaporated completely. The obtained powder was placed in a tube furnace in an oxygen atmosphere and sintered at 380 ° C for 6 to 9 hours. It was then cooled, dried, crushed and graded to obtain a compacted density of 3.7 g / cm 3 The positive electrode material is lithium titanium phosphate coated LiNi 0.8 Co 0.1 Mn 0.1 O 2 .
[0028] In the present invention, by adopting a fast and slow two-stage stirring method in the preparation of the precursor, the stirring speed and time are controlled, so as to achieve the effect of controlling the particle size distribution and shape of the secondary particles of the positive electrode material. The distribution width is affected by both the fast stirring speed and the slow stirring time, while the sphericity is mainly affected by the fast stirring speed. Both the stirring time and the stirring speed need to be controlled within a reasonable range. If the stirring time is too short, the small particles cannot be fully grown, and the effect of the concentrated particle size distribution cannot be achieved. If the stirring time is too long, the overall particle size of the primary particles is too large, which is not conducive to the rate performance and wastes resources. If the stirring speed is too small, the reaction is not sufficient, which is not conducive to the formation of secondary particles with a concentrated particle size distribution and a spherical shape. If the stirring intensity is too large, it is easy to cause the grown primary particles to be broken and generate fine powder, which is also not conducive to the formation of secondary particles with a concentrated particle size distribution.
[0029] 2. Preparation of positive electrode sheet
[0030] The prepared positive electrode material (core material chemical formula is LiNi0.8 Co 0.1 Mn 0.1 O 2 , the coating layer thickness H is 15nm, the particle sphericity S is 1, and the particle size D50 is 16μm) and the conductive agent acetylene black and the adhesive polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 95:3:2 to obtain a positive electrode slurry; the positive electrode slurry is coated on the aluminum foil of the positive electrode current collector, and the coating surface density is 2.5g / dm 2 , and then dried, cold pressed and slit to obtain the positive electrode sheet.
[0031] In some specific embodiments, the conductive agent may also be any one or more of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene, and Ketjen black. Similarly, in some embodiments, the adhesive may also be any one or more of polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, and polyvinyl alcohol.
[0032] 3. Preparation of negative electrode sheet
[0033] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 96:1:1.5:1.5 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector Cu foil, and the negative electrode sheet is obtained after drying, cold pressing, and stripping.
[0034] 4. Preparation of isolation membrane
[0035] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0036] 5. Preparation of electrolyte
[0037] Lithium salt LiPF 6 A solution prepared with a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) at a mass ratio of 8:92 is used as an electrolyte for a lithium ion secondary battery.
[0038] 6. Preparation of lithium-ion secondary batteries
[0039] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in a packaging shell, the electrolyte is injected and packaged to obtain a lithium-ion secondary battery.
[0040] Parameter measurement method:
[0041] 1. Measurement of the thickness of the positive electrode material coating
[0042] After the positive electrode materials of the embodiments and comparative examples of the present application were imaged by a 600K scanning electron microscope (German ZEISS Sigma-02-33), the difference between the coating layer and the main material of the ternary spherical particles could be directly observed through the high-resolution imaging capability of the TEM perspective electron microscope, thereby measuring the thickness of the coating layer.
[0043] 2. Measurement of sphericity
[0044] After the positive electrode materials of the embodiments and comparative examples of the present application were imaged through a 500x scanning electron microscope (German ZEISS Sigma-02-33), about 200 to about 600 secondary particles of the positive electrode material with complete shapes and no obstructions were randomly selected from the electron microscopic image, and the maximum length a (major axis) of the secondary particles in the electron microscopic image was taken as the particle size, and the maximum length b (minor axis) of each particle perpendicular to the major axis in the microscope image was recorded, and the sphericity = b (minor axis) / a (major axis) * 100.
[0045] Table 1 shows the measured parameters and some process parameters of the positive electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 5. By adopting a fast and slow two-stage stirring method in the preparation of the precursor, the stirring speed and time are controlled to control the particle size distribution and sphericity of the secondary particles of the positive electrode material, and the amount of the coating layer raw material and the sintering time during the secondary sintering are adjusted to adjust the coating layer thickness of the positive electrode material. The positive electrode materials of Examples 1 to 6 and Comparative Examples 1 to 5 are all prepared to have a compacted density of 3.7 g / cm 3 Highly compacted material.
[0046] Table 1
[0047]
[0048] Performance Testing
[0049] 1. Rate performance test
[0050] After the batteries prepared in Examples 1-6 and Comparative Examples 1-5 were fully charged at x C and fully discharged at 1 C for 10 times, the batteries were fully charged at x C again, and then the negative electrode plates were disassembled and the lithium deposition on the surface of the negative electrode plates was observed. If no lithium deposition occurred on the negative electrode surface, the charging rate x C was increased by 0.1 C as a gradient and tested again until lithium deposition occurred on the negative electrode surface, and the test was stopped. The charging rate (x-0.1) C at this time was the maximum charging rate of the battery. The test results are shown in Table 2.
[0051] 2. Cycle performance test
[0052] Take 5 lithium ion secondary batteries prepared in the comparative example and the example, and repeatedly charge and discharge the lithium ion secondary batteries by the following steps, and calculate the cycle capacity retention rate of the lithium ion secondary batteries:
[0053] First, in an environment of 25°C, the first charge and discharge are performed, and constant current and constant voltage charging is performed at a charging current of 0.1C (i.e., the current value that completely discharges the theoretical capacity within 10 hours) until the upper limit voltage reaches 4.3V.
[0054] The battery was discharged at a constant current of 1 C until the final voltage reached 3 V, and the discharge capacity of the first cycle was recorded. Then, 100 charge and discharge cycles were performed, and the discharge capacity of the 100th cycle was recorded.
[0055] Cycle capacity retention rate = (discharge capacity at the 100th cycle / discharge capacity at the first cycle) × 100%.
[0056] Table 2 shows the test data of the batteries prepared in Examples 1-6 and Comparative Examples 1-5.
[0057] Table 2:
[0058] Examples Maximum charge rate (C) Cycle capacity retention rate % Example 1 4.4C 96% Example 2 3.6C 90% Example 3 4.0C 92% Example 4 4.3C 94% Example 5 3.8C 91% Example 6 4.2C 93% Comparative Example 1 2.7C 78% Comparative Example 2 3.0C 76% Comparative Example 3 3.2C 76% Comparative Example 4 2.1C 70% Comparative Example 5 2.4C 72%
[0059] Analysis of test experimental results: It can be seen from Examples 1-6 and Comparative Examples 1-5 in Table 1 that the positive electrode material provided by the present invention, due to the synergistic effect of the appropriate coating layer thickness, particle sphericity and particle size, ensures a high compaction density while avoiding particle breakage of the positive electrode material under high compaction, which leads to performance degradation. The positive electrode sheet prepared using the positive electrode material has good rate performance and cycle performance under the premise of having a high compaction density.
[0060] The above description is only a partial or preferred embodiment of the present invention. The above description cannot limit the scope of protection of the present invention. All equivalent transformations made using the contents of the present invention specification under the concept of an overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a core body and a coating layer located on the surface of the core body. The thickness H of the coating layer and the sphericity S of the particles of the positive electrode material satisfy the relationship: 4≤H*S≤15, the value range of H is 6nm≤H≤16nm, the value range of S is 0.6≤S≤1, and the particle size D50 of the positive electrode material is in the range of 6μm≤D50≤16μm.
2. The positive electrode material according to claim 1, characterized in that The value range of H is 12nm≤H≤15nm; the value range of S is 0.8≤S≤1; and the value range of D50 is 6μm≤D50≤16μm.
3. The positive electrode material according to claim 2, characterized in that The thickness H of the coating layer and the particle sphericity S of the positive electrode material satisfy the relationship: 9.6≤H*S≤15.
4. The positive electrode material according to claim 1, characterized in that The H is 15 nm; the S is 1; the D50 is 16 μm; Alternatively, the H is 6 nm, the S is 0.7, and the D50 is 6 μm; Alternatively, the H is 10 nm, the S is 0.8, and the D50 is 10 μm; Alternatively, the H is 15 nm, the S is 1, and the D50 is 6 μm; Alternatively, the H is 12 nm, the S is 0.8, and the D50 is 13 μm; Alternatively, the H is 6 nm, the S is 0.7, and the D50 is 16 μm.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that: The chemical formula of the core is Li a Ni x Co y M 1-x-y O2, wherein M is Mn and / or Al, 0.8≤a≤1.5, 0.6≤x≤1, 0≤y≤0.
2.
6. The positive electrode material according to claim 5, characterized in that The coating layer includes at least one of a metal oxide, a solid electrolyte, an electrode material, and a conductive polymer.
7. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 6.
8. The positive electrode sheet according to claim 7, characterized in that: The positive electrode active material layer further includes a conductive agent and a binder.
9. The positive electrode sheet according to claim 8, characterized in that: The conductive agent is selected from at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene, and Ketjen black; and / or, The adhesive is selected from at least one of polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate and polyvinyl alcohol.
10. A lithium ion battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 7 to 9.